Productive Response of Broiler Chickens Ross 308 Exposed to Different Feed Restriction Systems with/ without Dietary Anise and Fenugreek (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This experiment was carried to investigated the influence of using 3 different feed restriction systems with or without adding the dietary anise and fenugreek on productive performance of broiler chickens during the early age (2 and 3 weeks). It has been used 400 unsexed chicks (Ross 308) - one day old which distributed randomly into 10  treatments (40 chicks / treatment(assigned into 2 replications  (20 chicks/ replication).Chicks were reared for 6 weeks and divided at 2 week old into the following treatments:1st treatment (G1): Ad libitum feeding (control), 2nd, 3rd and 4th treatments (G2, G3 and G4): quantitative feed restriction (30%), 5th, 6th and 7th treatments (G5, G6 and G7): time feed rectriction (12 hours/day), 8th , 9th and  10th treatments (G8, G9 and G10):  diet dilution with sand (15%). 1% of  fenugreek powder was added to G3 , G6 and G9 diets and 1% of anise powder was added to G4, G7 and G10 diets.The results revealed that all feed restriction treatments led to maintain accumulatively (1- 6 weeks) the body weight, weight gain and growth rate accompanied with  lowering (P